Iron and Manganese Removal from Wastewater by Constructed Wetlands Planted with Caladium bicolor - Phuong, Nguyen Minh; Hai, Do Thi; Thanh, Nguyen Van; Anh, Bui Thi Kim (VNU Journal of Science: Earth and Environmental Sciences, 2022)
Constructed wetlands (CWs) have been applied to treat various wastewater types including domestic wastewater, livestock wastewater, industrial wastewater and acid mine drainage with the advantages of low cost, environmentally-friendly technology and high treatment efficiency. Mining wastewater with the high content of heavy metals often causes negative impacts on the ecosystems and human health. In this study, the capacity of using limestone, hydrolyzed rice husk as filter materials and the CWs planted with Caladium bicolor to treat iron and manganese in artifical wastewater treatment are evaluated. The wetland model has the size of length x width x height of 50 cm x 15 cm x 20 cm. 10 liters of the synthetic wastewater were used and initial Fe and Mn concentrations varied from 5, 10, 15, 20 and 25 mg/L. The results showed that limestone and hydrolyzed rice husk with the weight ratio of 5 : 2.5 (kg) had good ability to remove Fe and Mn with treatment efficiencies of approximately 99.8% after 144 hours. During a 24-hour retention time, the Fe and Mn concentrations ​​in the wastewater decreased rapidly in CWs and the initial Fe and Mn concentrations affected treatment performance. When the initial Fe and Mn concentrations were below 20 mg/L, treatment efficiencies of Fe and Mn reached about 99% after 144 hours in the CWs and Fe and Mn concentrations met the national regulation QCVN 40: 2011/BTNMT, column B. The study highlights the potential applications of C. bicolor in CWs with the use of natural limestone and hydrolyzed rice husk as substrates in treatment of iron and manganese-contaminated wastewater. Keywords: Constructed wetlands, Caladium bicolor , limestone, rice husk, iron, manganese.